Japan as number one : - Vogel, Ezra F. (Harper & Row, 1980)
Based on the most up-to-date sources, as well as extensive research and direct observation, Japan as Number One analyzes the island nation's development into one of the world's most effective industrial powers, in terms of not only economic productivity but also its ability to govern efficiently, to eduate its citizens, to control crime, to alleviate energy shortages, and to lessen pollution. Ezra Vogel employs criteria that America has traditionally used to measure success in his thoughtful demonstration of how and why Japanese institutions have coped far more effectively than their American counterparts.